2011
DOI: 10.1080/17448727.2011.593299
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Substance Abuse and Intimate Partner Violence in Punjabi Sikh Communities

Abstract: This article outlines the importance of exploring spirituality in working with Punjabi Sikh men who have substance abuse issues and have committed violence towards their spouse. Seventeen in-depth interviews were conducted with South Asian front-line workers that included police officers, probation officers, counselors, social workers, child protection workers and victim service workers. The audio-taped data were transcribed and analyzed by identification of themes and subthemes. Participant comments around re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Similar to existing literature, participants found that SAs prefer not to be involved in social issues like DV and were in denial that abuse happens (see Abraham, 2000; Dasgupta, 2000, 2007; Thandi, 2011). When some women, such as Asha and Preet, approached the SA community for help, they were made to feel they had erred.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Similar to existing literature, participants found that SAs prefer not to be involved in social issues like DV and were in denial that abuse happens (see Abraham, 2000; Dasgupta, 2000, 2007; Thandi, 2011). When some women, such as Asha and Preet, approached the SA community for help, they were made to feel they had erred.…”
Section: Resultssupporting
confidence: 70%
“…While MSOs aim to be inclusive of all abused women regardless of specific community or culture, the women I interviewed expressed a strong need for culturally and linguistically appropriate services. Their suggestions for interpreters and resources in various languages echo existing literature (Chokshi et al, 2010;Guruge & Humphreys, 2009;Menjivar & Salcido, 2002;Thandi, 2011). Three participants recommended hiring more SA staff familiar with various cultural backgrounds.…”
Section: Support From Msos and Sawosmentioning
confidence: 52%
See 2 more Smart Citations
“…Some studies suggest that people who report higher religiosity are less likely to engage in alcohol and drug use (Delaney et al, 2009, Geppert et al, 2007, Hodge et al, 2007, Koenig et al, 2001. Studies relating to Sikhism in particular found that people who were striving to overcome alcohol problems were re-engaging with Sikhism to support them with their recovery through increased religious involvement, for example, performing Sewa (service) within the community and the recitation of sacred texts (Morgaria and Orford, 2002, Morjaria-Keval, 2006, Sandhu, 2009, Thandi, 2011.…”
Section: Sikhism and A Punjabi Drinking Culturementioning
confidence: 99%